2022
DOI: 10.1021/acs.jpclett.2c00231
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids Are Driven to the Interface by Salts and Acidic Environments

Abstract: Amino acids (AAs), the building blocks of proteins, are enriched by several orders of magnitude in sea spray aerosols compared to ocean waters. This suggests that AAs may reside at the air–water interface and be highly surface active. Using surface tension measurements, infrared reflection–absorption spectroscopy, and molecular dynamics simulations, we show that AAs are surface active and that salts and low-pH environments are drivers of surface activity. At typical sea spray salt concentrations and pH values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…Now, we review our results in the context of previous literature. The strong salting-out of the charged species has previously been reported for charged surfactants (47)(48)(49). The surfactants have a hydrophobic part, which is exposed to the air at the water-air interface.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Now, we review our results in the context of previous literature. The strong salting-out of the charged species has previously been reported for charged surfactants (47)(48)(49). The surfactants have a hydrophobic part, which is exposed to the air at the water-air interface.…”
Section: Discussionmentioning
confidence: 65%
“…Our generalization suggests that this salting-out can occur not only for the typical ions but also for the charged molecules. In fact, it has been reported that the surfactants/lipids tend to appear at the interface upon the addition of salt (47)(48)(49). This phenomenon can be understood as the more hydrophobic surfactant tends to appear at the interface because the ions which are generated by dissolving salt into water push the surfactant in the bulk away to the interface.…”
Section: Discussionmentioning
confidence: 99%
“…Similar correlations between amino acids and the time spent by the air mass over the sea and continental surfaces within the ABL have been observed by (Renard et al., 2022). Even though amino acids (directly measured in cloud water samples) and ProteinC (a statistical category of protein) should be compared with caution, sea salt may drive amino acids to the aerosol−air interface, where they can more readily undergo chemical reactions, including peptide formation under certain conditions (Angle et al., 2022). These consistent correlations may confirm direct influences from the boundary layer in terms of nitrogen supply.…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by our recent work where we found that formic acid is as effective as ammonia for the formation of clusters with sulfuric acid and water . Including water molecules results in the formation of hydrogen-bond networks. , Sulfuric acid can form comparably stable clusters with atmospheric species other than bases, such as formic acid , and amino acids. In these cases, the ability of functional groups to form strong intermolecular interactions is key to the thermodynamic stability of the cluster. , Amino acids are enriched in sea spray aerosols by up to 7 orders of magnitude, and they are driven to the aerosol air–water interface in salts and acidic environments . At the interface, they are more reactive, including for the formation of peptide bonds. Yet, amino acids without the presence of sulfuric acid do not drive aerosol formation .…”
Section: Introductionmentioning
confidence: 93%
“…36,37 Amino acids are enriched in sea spray aerosols by up to 7 orders of magnitude, 38 and they are driven to the aerosol air−water interface in salts and acidic environments. 39 At the interface, they are more reactive, including for the formation of peptide bonds. 40−43 Yet, amino acids without the presence of sulfuric acid do not drive aerosol formation.…”
Section: ■ Introductionmentioning
confidence: 99%